Self-Report Measures in the Assessment of Antiretroviral Medication Adherence - Lassane Kabore PharmD, MSc, MSPH; Paul Muntner PhD; Eric Chamot MD, PhD; Anne Zinski PhD; Greer Burkholder MD, MSPH; Michael J. Mugavero MD, MHSc (Journal of the International Association of Providers of AIDS Care, 2015)
Background: Adherence is a major determinant of the effectiveness of antiretroviral therapy (ART). We determined the association between self-reported adherence (SRA) and medication possession ratio (MPR), a pharmacy-based adherence measure, and their respective associations with viral load. Methods: Adherence to ART was assessed by MPR over 6 months and by self-report which included a question with a Likert-type scale response, a visual analogue scale (VAS), and an inquiry about the last time the patients skipped any prescribed medications. Results: Taking MPR as the “gold standard,” all 3 SRA measures displayed high specificity but low sensitivity. The prevalence ratio (95% confidence interval) for viral load ≥50 copies/mL was 2.19 (1.07-4.50) for MPR <90%, 1.98 (1.04-3.78) for poor/fair/good versus excellent/very good ability to take antiretroviral drugs, 1.47 (0.79-2.75) for skipping medications within the past 2 weeks, and 2.51 (1.39-4.53) for VAS <95%. Conclusion: These data suggest various SRA measures hold clinical value in screening for poor ART adherence.